2022
DOI: 10.1021/acsami.2c12553
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Electrochemistry-Induced Detachable Adhesives with Ultra-High Bonding Strength and Detaching Efficiency

Abstract: Detachable adhesives with simultaneously high bonding strength and detaching efficiency have remained a great challenge in adhesion science. The existing detachable adhesives (e.g., solid–liquid phase transitions-based adhesives) usually show low initial cohesion and require long detaching time (several minutes or hours for transitions). Herein, by introducing ionic liquids (ILs) and soft polyethylene glycol (PEG) into a rigid epoxy precursor and curing, we demonstrated the adhesives with both high initial bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Figure G displays the relations between the detaching efficiency (Ψ [60 V,30 s] and Ψ [60 V,60 s] ) and ionic conductivity (σ); it is found that the electrically detaching behavior of IEPs is positively related to the ionic conductivity and it is consistent with our previously published work . It also can be explained that the strong crystallization of PEG2000 significantly limits the ion migrations under an electric field, which hinders the interfacial electrochemical reactions.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Figure G displays the relations between the detaching efficiency (Ψ [60 V,30 s] and Ψ [60 V,60 s] ) and ionic conductivity (σ); it is found that the electrically detaching behavior of IEPs is positively related to the ionic conductivity and it is consistent with our previously published work . It also can be explained that the strong crystallization of PEG2000 significantly limits the ion migrations under an electric field, which hinders the interfacial electrochemical reactions.…”
Section: Resultssupporting
confidence: 87%
“…Moreover, a semicircle and a following straight line are observed for all IEP-M 15–10 from the Nyquist plots (Figure B), indicating that the ion conduction of ionic liquids in IEPs is a typical Faradic process . An equivalent circuit was used to simulate the electrochemical impedance spectroscopy (EIS) results (Figure S5), which contains two constant-phase elements (CPE) and three resistors including contact resistance ( R c ), ion transfer resistance ( R b ), and interfacial resistance ( R i ) . According to this model, the ionic conductivity (σ) of IEP- M 15–10 gradually decreases from 7.5 × 10 –5 to 4.04 × 10 –5 S·m –1 with the PEG molecular weight increasing from 200 to 1000 g·mol –1 , while it sharply decreases to 4.62 × 10 –7 S·m –1 when the PEG molecular weight reaches 2000 g·mol –1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations